Capitalism as culture and statecraft: Weber– Simmel–Hirschman. (February 2013) - Scott, Alan
This paper offers a critical exposition and a comparison of the arguments of three key thinkers – Max Weber, Georg Simmel and Albert Hirschman – who rejected purely economic accounts of the development and nature of capitalism – whether Marxist or neo-classical – and sought to develop an account of capitalism as culture; as a form of life, conduct, an ethic, a system of ideas and ideals. Such approaches are characterized by (i) their emphasis on the resistance that capitalism faced, and continues to face; (ii) the examination of capitalism at the level of meaning and experience; and (iii) an interest in its institutional and cultural framing. Both the similarities and points of disagreement between these three accounts are discussed. Taking up David Frisby's concern with Simmel's politics – Frisby being the dedicatee of this special issue – the paper concludes by focusing on Simmel's 'sociological ambivalence' in his analysis of the money economy as the source both of greater personal freedom and of the fracturing of personality and growing subservience to 'objective culture'.